Comparing DNA metabarcoding with faecal analysis for diet determination of the Eurasian otter (Lutra lutra) in Vejlerne, Denmark - Pertoldi, Cino; Schmidt, Jakob Braüner; Thomsen, Patrick Møller; Nielsen, Louise Bach; de Jonge, Nadieh; Iacolina, Laura; Muro, Federico; Nielsen, Kristian Trøjelsgaard; Pagh, Sussie; Lauridsen, Torben Linding; Andersen, Line Holm; Yashiro, Erika; et al. (Mammal research, 2021)
The Eurasian otter ( Lutra lutra ) is a semi-aquatic predator that lives in a wide range of aquatic habitats. Knowledge of the diet of predators is essential for the management and conservation of the species and their habitats. We assessed the diet of otters in fifty-three faecal samples (spraints) by morphological analysis of undigested prey remains and by DNA metabarcoding approaches with two different blocking primers. The blocking primers were shown to be similarly effective in repressing host DNA, improving amplification of non-host taxa. The analyses were conducted to compare the accuracy of the two methods. The prey items were categorized to the highest possible taxonomic resolution, and relative frequency of occurrence was applied in order to compare the morphological and DNA results. The bulk score for difference prey items in the spraints was based on volume estimates in macroscopic observations. The two methods had an overlap of identified prey species ranging from 69.9 to 72.9% (depending on the kind of primers) meaning that a large portion of prey items found by one method was replaced by other prey items in the other method and that most prey items found through DNA-metabarcoding are considered new when compared with the morphological analysis. Therefore, applying both morphological and DNA analysis is crucial in order to determine the diet of otters and, possibly, other predatory species.